Characterization of packed-bed in the downcomer of a concentric internal-loop airlift bioreactor - Mazziero, Vítor Teixeira [UNESP]; Batista, Vinícius Guerso [UNESP]; Oliveira, Daniele Gonçalves de [UNESP]; Scontri, Mateus [UNESP]; de Paula, Ariela Veloso [UNESP]; Cerri, Marcel Otavio [UNESP] (Elsevier, 2022)
A packed-bed basket containing corn cob powder was used for the adaptation of a concentric-tube airlift reactor for enzymatic reactions. The bed was inserted in the downcomer region of the bioreactor generating a decrease in liquid downflow. To characterize the liquid velocity through the packed-bed and calculate the residence time, the intrinsic permeability was determined using Darcy's law, resulting in 1.275 × 10−9 m2 (40-mesh particle size), and the pressure difference was calculated using the riser gas holdup, reaching values up to 56.6% for water at 3.5 vvm. Thus, a superficial liquid velocity model was obtained to describe the liquid velocity at different airflow rates and bed lengths, covering a wide range of support masses commonly used in enzymatic reactions. The model also allows the variation of viscosity, caused by different reaction temperatures and the use of larger bed sizes for scaling. Using the dye tracer method, it was possible to visualize the flow through the bed and corroborate the residence times obtained by the model for a wide range of airflows. Therefore, it describes the use of a basket filled with potential enzyme support, contributing to the applicability of pneumatic systems as enzymatic bioreactors, particularly internal-loop airlift reactors.
Keywords: 3D printed; Enzymatic bioreactor; Gas holdup; Packed-bed permeability